Role of intratumoral lymphatic vessels in the lymph node dissemination of laryngopharyngeal squamous cell carcinoma - Hinojar Gutiérrez, Adolfo; Fernández Contreras, María Encarnación; Álvarez Carrillo, S.; Quintanilla, M.; Gamallo, C. (My University, 2010)
Background. The development of new markers for lymphatic endothelium allowed the study of intratumoral lymphatic microcirculation, as well as its association with lymph node metastasis. Methods. In all, 120 patients with laryngopharyngeal squamous cell carcinoma (LPSCC) without previous treatment were retrospectively studied. The immunohistochemical determination of PA2.26 antigen/podoplanin was used to assess intratumoral lymphatic vessels (ILVs) in the primary tumor. Results. Multivariate analysis revealed that lymph node metastasis was associated with tumor location (p = .001), differentiation grade (p = .02), and ILV (p = .013). Hypopharyngeal and supraglottic locations, poor grade of differentiation, and ILV, respectively, increased the risk of developing lymph node metastasis 13.5-, 4.7-, 5.2-, and 3.2-fold. Conclusions. In our series, the presence of ILV in the primary tumor was an independent risk factor for the development of lymph node metastasis. The incorporation of ILV assessment into routine clinicopathological study might improve the evaluation of patients with LPSCC.